Analisis Yuridis Kartel Defensif dalam Perspektif Hukum Persaingan Usaha Indonesia - Surahman; Paturu', Reny Oktaviani (Universitas Bojonegoro, 2026)
Cartels are a form of agreement that is prohibited under competition law because they have the potential to lead to monopolistic practices and unfair competition. However, in practice, a phenomenon known as a defensive cartel has emerged, which is an agreement between business actors that is claimed to be aimed at maintaining industry stability or responding to external pressures, but has the potential to distort market mechanisms. This study aims to analyze the position of defensive cartels from the perspective of Indonesian competition law and to assess the application of the rule of reason principle by the Business Competition Supervisory Commission (KPPU). The research method used is normative juridical with a regulatory, conceptual, and case approach. The results of the study show that Indonesian competition law does not provide normative justification for defensive cartels, so that any agreement that meets the elements of Article 11 of Law Number 5 of 1999 still has the potential to be declared unlawful. The rule of reason principle opens up space for assessing the impact of competition and efficiency claims, but its implementation has not been optimal due to difficulties in proving22, particularly in relation to the use of circumstantial evidence. Therefore, it is necessary to strengthen the evidence mechanism and reformulate the cartel law enforcement policy to ensure the protection of business competition and consumer interests.